Identification of Aortic Proteins Involved in Arterial Stiffness in Spontaneously Hypertensive Rats Treated With Perindopril:A Proteomic Approach - Miotto, Danyelle S.; Dionizio, Aline; Jacomini, André M.; Zago, Anderson S.; Buzalaf, Marília Afonso Rabelo; Amaral, Sandra L. (Frontiers in Physiology, 2021)
Arterial stiffness, frequently associated with hypertension, is associated with disorganization of the vascular wall, and has been recognized as an independent predictor of all-cause mortality. The identification of the molecular mechanisms involved in aortic stiffness would be an emerging target for hypertension therapeutic intervention. This study evaluated the effects of perindopril on pulse wave velocity (PWV) and on the differentially expressed proteins in aorta of spontaneously hypertensive rats (SHR), using a proteomic approach. SHR and Wistar rats were treated with perindopril (SHRP) or water (SHRc and Wistar rats) during 8-weeks. At the end, SHRC presented higher systolic arterial pressure systolic blood pressure (SBAP,+70%) and PWV (+31%) compared with Wistar rats. SHRP had higher values of nitrite concentration and lower PWV compared with SHRC. From 21 upregulated proteins in the aortic wall from SHRC, most of them were involved with the actin cytoskeleton organization, like Tropomyosin and Cofilin-1. After perindopril treatment, there was an upregulation of the GDP dissociation inhibitors (GDIs), which normally inhibits the RhoA/Rho-kinase/cofilin-1 pathway and may contribute to decrease arterial stiffening. In conclusion, the results of this present study revealed that treatment with perindopril reduced SAP and PWV in SHR. In addition, the proteomic analysis in aorta suggested, for the first time, that RhoA/Rho-kinase/Cofilin-1 pathway may be inhibited by perindopril-induced upregulation of GDIs or increases in NO bioavailability in SHR. Therefore, we may propose that activation of GDIs or inhibition of RhoA/Rho-kinase pathway could be a possible strategy to treat arterial stiffness.